2017
DOI: 10.1039/c7bm00244k
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular accumulation and immunological responses of lipid modified magnetic iron nanoparticles in mouse antigen processing cells

Abstract: Understanding the effects of magnetic iron nanoparticles (MINPs) on the immune response is vitally important for biomedical applications such as cancer therapy, disease diagnosis and novel cancer imaging. In this study, lipid modified MINPs were designed and prepared by introducing the neutral lipid DSPE-PEG or the zwitterionic lipid DSPE-PCB into hydrophobic MINPs through hydrophobic interaction (L-MINPs and ZL-MINPs, respectively). The effect of L-MINPs and ZL-MINPs on the intracellular accumulation and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…According to previous literature, the delivery efficiency of antigens has a direct effect on the ability to induce the level of immune response [32,33]. So we speculate that it is a very effective strategy to improve the delivery efficiency of antigens through controlling the releasing process of antigen, so as to avoid the metabolism loss caused by the one-time high dose injection of antigens.…”
Section: Cnf-induced Humoral Immune Responses In Vivomentioning
confidence: 87%
“…According to previous literature, the delivery efficiency of antigens has a direct effect on the ability to induce the level of immune response [32,33]. So we speculate that it is a very effective strategy to improve the delivery efficiency of antigens through controlling the releasing process of antigen, so as to avoid the metabolism loss caused by the one-time high dose injection of antigens.…”
Section: Cnf-induced Humoral Immune Responses In Vivomentioning
confidence: 87%
“…NPs coated with 3-(dimethylamino)propylamine-substituted poly(maleic anhydride-alt-1-decene) did not induce a change in cytokine or chemokine levels [24] whereas NPs coated with distearoylphosphoethanolamine-polycarboxybetaine (DSPE-PCB) induced a strong mixed Th1/Th2 type immune response but did not change the IL-10 level. [25] In both cases, NPs were not tested for bacterial endotoxin.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, C6 cells were exposed to CPDs at different concentrations (50–200 μg mL –1 ) for 1 h. The cellular uptake of CPDs would also enhance when increasing the concentration of CPDs (Figure B). These results suggested that the internalization of CPDs into C6 cells involved in time- and dose-dependent procedures was consistent with the behaviors of other nanoparticles. …”
Section: Resultsmentioning
confidence: 78%